Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1016/0009-2614(91)80161-p
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the primary electron transfer in photosynthetic reaction centers from Rhodobacter sphaeroides

Abstract: The resonance-enhanced multiphoton ionization (REMPI) of the OH radical in the gas phase was studied using an isothermal discharge-flow reactor for the production of OH radicals (H+NO,+OH+NO), tunable laser light from an excimer-pumpeddye laser, and a time-of-flight (TOF) mass spectrometer. A mass-resolved REMPI spectrum was found in the wavelength region of 290-3 10 nm, which is assigned to a (3 + I ) ionization process. An ab initio quantum-chemical calculation predicts the Rydberg state, verified by the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 28 publications
4
63
0
Order By: Relevance
“…Very recent emission experiments have shown that the 3 ps decay of P* seems to be a biphasic process with two time constants [8,9]. At all temperatures an additional subpicosecond component was detected in Rhodobacter sphaeroides having time constants of 0.3 ps to 0.9 ps for temperatures of 25 K to 300 K [10,11]. The same ultrafast component was found in RCs from Rhodopseudomonas viridis having a time constant of 0.65 ps at 300 K [5].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Very recent emission experiments have shown that the 3 ps decay of P* seems to be a biphasic process with two time constants [8,9]. At all temperatures an additional subpicosecond component was detected in Rhodobacter sphaeroides having time constants of 0.3 ps to 0.9 ps for temperatures of 25 K to 300 K [10,11]. The same ultrafast component was found in RCs from Rhodopseudomonas viridis having a time constant of 0.65 ps at 300 K [5].…”
Section: Introductionmentioning
confidence: 72%
“…0.9 ps) is associated with the electron transfer from P+B A to P+H A (The assignment of ~3 = 200 ps to the transition of P+H A to P+Q;~, on the other hand, is generally accepted). Regarding the sub-picosecond kinetic ~'2, one trivial explanation could not be ruled out: All published experiments where a sub-picosecond kinetic (namely ~2) was observed, were done with detergenttreated preparations of isolated RCs [2,6,7,10]. It is not known whether the ultrafast absorption dynamics are altered by a preparation artifact during the isolation of the reaction centers from the chromatophores by detergents.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we present kinetic absorption studies on RCs containing 132-hydroxy-BChl-a or [3-vinyl] system has been described in detail (19) are plotted for Apr = 920 nm, Apr = 785 nm, and Apr = 665 nm.…”
Section: P+b P+h-p+q- This Model Ismentioning
confidence: 99%
“…The observation of an additional, subpicosecond time constant in Rhodobacter sphaeroides (16)(17)(18)(19)(20) again raised the possibility of P+B-being a real intermediate according to P .…”
mentioning
confidence: 99%
“…It now is becoming accepted that electron transfer from P* to P ϩ H A Ϫ proceeds via the anion of the accessory Bchl, B A , located between P and H A . At room temperature P ϩ B A Ϫ is formed as a short-lived, intermediate with a lifetime of 0.9-1.5 ps (7)(8)(9)(10)(11). Charge separation is completed by electron transfer from P Until recently it generally was accepted that excitation of the RC bacteriopheophytins or monomeric Bchls resulted in downhill energy transfer to P within a few hundreds of femtoseconds, forming P* that drives charge separation (12)(13)(14)(15).…”
mentioning
confidence: 99%